Antioxidant Activity and In Vitro Antiglycation of the Fruit of Spondias purpurea. (29th August 2018) - Muñiz, Alethia; Garcia, Efren; Gonzalez, Daphne; Zuñiga, Lizette
Abstract : Hyperglycemia in diabetes mellitus causes irreversible life-threatening micro- and macrovascular complications. There is evidence that the glycation reaction leads to a chemical modification of the proteins contributing to the complications of diabetes. It is known that advanced glycation end products (AGEs) are formed by glycation and oxidation reactions called glycoxidation. CML, a nonfluorescent AGE, has become a biomarker of glycoxidative damage; other AGEs appear to induce oxidative stress, which results in cytotoxicity. To determine antioxidant activity, the FRAP, DPPH, and TEAC tests were used, as well as the polyphenols content using Folin-Ciocalteu's method. To evaluate the antiglycation activity, the BSA/glucose system was used, and the fructosamine concentration, protein carbonyl content, thiol, and CML groups were determined. The results obtained show that the hexane extract of the fruit of Spondias purpurea (CFH) effectively inhibits the glycation reaction, in addition to increasing the thiol groups and decreasing levels of fructosamine, protein carbonyl, and CML. In addition, CFH presented significant antioxidant activity. CFH inhibits the glycation reaction; therefore, it can help prevent complications related to AGEs in diabetes mellitus; it also reduces oxidative stress and is effective in protecting proteins from oxidative damage.